2019
DOI: 10.1098/rspb.2018.2313
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of good genes sexual selection under environmental change

Abstract: Sexual selection can promote adaptation if sexually selected traits are reliable indicators of genetic quality. Moreover, models of good genes sexual selection suggest that, by operating more strongly in males than in females, sexual selection may purge deleterious alleles from the population at a low demographic cost, offering an evolutionary benefit to sexually reproducing populations. Here, we investigate the effect of good genes sexual selection on adaptation following environmental change. We show that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 66 publications
(86 reference statements)
1
30
2
Order By: Relevance
“…In addition, Martinossi‐Allibert et al . (2019 a ) recently showed that rapid environmental change can in principle result in less‐effective good‐genes sexual selection, at least in species where sexual selection takes place in small‐ to medium‐size organisms (i.e. applicable to most animal species in the wild).…”
Section: Framework For the Study Of Temperature And Sexual Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Martinossi‐Allibert et al . (2019 a ) recently showed that rapid environmental change can in principle result in less‐effective good‐genes sexual selection, at least in species where sexual selection takes place in small‐ to medium‐size organisms (i.e. applicable to most animal species in the wild).…”
Section: Framework For the Study Of Temperature And Sexual Selectionmentioning
confidence: 99%
“…Martinossi‐Allibert et al ., 2018). Briefly, because female fitness depends on fecundity selection while male fitness depends on their ability to monopolise fertilizations within a mating patch, group size poses an upper limit for male (but not female) variance (Martinossi‐Allibert et al ., 2019 a ). By contrast, there is substantial theoretical and empirical work showing that genomic conflict between the sexes should be ameliorated in populations facing environments to which they are not adapted, hence increasing population adaptation (e.g.…”
Section: Framework For the Study Of Temperature And Sexual Selectionmentioning
confidence: 99%
“…Sexual selection can impose substantial fitness costs at the individual level, especially in low‐quality habitats (Janicke et al, ; Martinossi‐Allibert, Rueffler, Arnqvist, & Berger, ), with consequences for the dynamics of populations. We acknowledge that our study does not explicitly investigate the role of potential environmental drivers on the pattern of sexually selected traits.…”
Section: Discussionmentioning
confidence: 99%
“…Rice 1992, Chippindale et al 2001, Pischedda and Chippindale 2006, Prokop et al 2012, or on SC genetic variation, which many theoretical models on the benefits of sex assume (e.g. Manning 1984, Kodric-Brown and Brown 1987, Agrawal 2001, Siller 2001, Lorch et al 2003, Martinossi-Allibert et al 2019a).…”
Section: Introductionmentioning
confidence: 99%